1984
DOI: 10.1002/jsfa.2740350417
|View full text |Cite
|
Sign up to set email alerts
|

Flour components affecting paste and noodle colour

Abstract: The influence of components contributing to the colour and brightness of flour, flour paste and Chinese and Japanese style noodles has been investigated. Differences in brightness and yellowness were attributable to wheat cultivar, milling extraction rate, protein content, starch damage and brown and yellow pigments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
118
1
1

Year Published

1992
1992
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(129 citation statements)
references
References 3 publications
9
118
1
1
Order By: Relevance
“…29,30 During storage of raw noodles, oxidizing enzymes present in the flour convert the free phenolic compounds to quinones, which are subsequently converted to dark melanins, which cause grey discoloration in noodle sheets. 28 The genotypes used in this study innately possessed high PPO content (data not shown) and, consequently, underwent excessive discoloration during storage. The rate of discoloration was most profound in the highly sprouted sample C1, possibly due to sprout-induced increased PPO levels in the bran region.…”
Section: Effect Of Pearling On Noodle Sheet Colourmentioning
confidence: 99%
“…29,30 During storage of raw noodles, oxidizing enzymes present in the flour convert the free phenolic compounds to quinones, which are subsequently converted to dark melanins, which cause grey discoloration in noodle sheets. 28 The genotypes used in this study innately possessed high PPO content (data not shown) and, consequently, underwent excessive discoloration during storage. The rate of discoloration was most profound in the highly sprouted sample C1, possibly due to sprout-induced increased PPO levels in the bran region.…”
Section: Effect Of Pearling On Noodle Sheet Colourmentioning
confidence: 99%
“…steamed and fried or steamed and dried. Consideration of colour is more important with raw noodles than with boiled or steamed noodles, since time-dependent darkening due to polyphenolic oxidases (PPO) may occur (Miskelly 1984 (Miskelly 1984 Ltd., Tokyo, Japan) to prepare the noodles (Oh et al 1983;Miskelly and Moss 1985;Shelke et al 1990 (Fig. 1, bottom) yellowness upon overnight storage, much as is shown in Fig.…”
mentioning
confidence: 99%
“…Flour color includes complex attributes, such as pigments of starchy endosperm, pericarp and pigments in the aleurone of wheat grain, as well as the flour extraction ratio, particle size, protein and ash content, and microbial contamination (Miskelly, 1984;Mares & Campbell, 2001). The brightness of flour decreases with increase of the particle size as well as the protein, ash, damaged starch and tailing starch content, which causes dull color in white salted noodles (Huo, 2001;Fu, 2008).…”
Section: Introductionmentioning
confidence: 99%